Determining equivalent charges on flow and balance in individual account pension systems - Luis Chávez-Bedoya (Journal of Economics, Finance and Administrative Science, 2016)
In this article, we determine a charge on balance that is equivalent to a certain fixed charge on flow for a particular utility–maximizer affiliate participating in a defined-contribution pension fund under the system of individual accounts. We also prove, under market completeness, that the equivalent charge on balance depends only on the current level of the charge on flow, the length of the accumulation period and the risk free rate of return. – – En este artículo se determina una exacción en el balance, que es equivalente a cierta tasa fija en el flujo de una empresa asociada particular maximizadora, que participa en un fondo de pensiones de aportación definida en el sistema de cuentas individuales. También se prueba, en la integridad del mercado, que la exacción de tipo equivalente en el balance depende solo del nivel actual de la tasa en el flujo, la duración del período de acumulación y un tipo de rentabilidad sin riesgo.
Keywords: G23; 330; Pension fund; Defined benefit; Individual account; Charge on balance; Charge on flow; Fondo de pensiones; Beneficio definido; Cuenta individual; Exacción en el balance; Exacción en el flujo